From Poverty to Assimilation: Thomas Jefferson on Native Americans as Indigent People - Vajda, Zoltán (Hungarian Journal of English and American Studies, 2022)
Thomas Jefferson has long been noted for his vested academic interest in Native Americans, whom he considered to be a doomed, yet, through assimilation, a redeemable race—who in his view were people living in poverty; an aspect of Jefferson’s vision of the indigenous peoples of North America which has so far been ignored. This essay therefore claims that Jefferson’s general concern with them was also fueled by his understanding of Native Americans as people whose way of life relegated them into the condition of indigence by definition—a state Jefferson wished to alleviate. Drawing on Jefferson’s ideas of political economy, combined with a perspective provided by early American poverty studies, I argue that his republican ideal of free-holding male household heads was also a key to his conception of Native American poverty as well as to his solution to it. In his view, gender roles and practices within the Native communities prevented male heads from adapting to the Euro-American ideals. In Jefferson’s eyes, women’s contribution to basic activities of sustenance, thus, rendered their spouses incapable of providing for their families by the Euro-American standard of the gender division of labor. He regarded them as indigents because of their actual mode of sustenance, but a desirable shift to white ways, Jefferson implied, held the promise for them to get out of destitution. (ZV)